The Acute and Chronic Toxicity of Copper on The Behavioral Responses and Hematological Parameters of Freshwater Fish, Common Carp (Cyprinus carpio L.) - Hatem Al-Tamimi, Ahmed; J. Al-Azzawi, Ahmed (Iraqi Journal of Science, 2023)
The present study was conducted to examine toxicological effects of copper sulfate (Cu) in common carp fish (Cyprinus carpio L.). The LC50 (median lethal concentrations) of copper on Cyprinus carpio were 3.64, 3.36, 3.04, 2.65 mg/L respectively. In general, behavioral responses of the fishes exposed to copper included uncontrolled swimming, erratic movements, loss of balance, swam near the water surface with sudden jerky movements. Haematological parameters such, red blood cells (RBC), white blood cells (WBC), haemoglobin (Hb), Packed cell volume (PCV), mean cell volume (MCV) mean cell haemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) were studied. The obtained results indicated that the (RBC) and (WBC) have increased with increasing metal concentrations and exposure period. While, haemoglobin (Hb) had slightly increased compared with control fish. Other parameters like Packed cell volume (PCV), mean cell volume (MCV) mean cell haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) appeared likely being enhanced with increased exposure to studying heavy metals, and did not show any significant increase with different concentrations used in chronic exposure experiments.